2011
DOI: 10.1111/j.1439-0418.2011.01692.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature influences the expression of resistance of soybean (Glycine max) to the soybean aphid (Aphis glycines)

Abstract: Resistance of plants to arthropods may be lost at low or high temperatures. I tested whether the relative resistance of five genotypes of soybean, Glycine max (L.) Merr., to three isolates of the soybean aphid, Aphis glycines Matsumura, was influenced by three temperatures, 14, 21 and 28°C, in no‐choice tests in the laboratory. The interaction between temperature and the genotype of soybean influenced the population sizes of two isolates of A. glycines. Two genotypes of soybean, LD05‐16611 and PI 567597C, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Our results also contrasted with another report that indicated resistance in LD05-16611 (Rag1) to aphid biotypes 1 and 3 was ineffective at 14°C (Richardson, 2012). Results in this study indicated that resistance expression in LD05-16611 kept aphid populations at similar levels in all three temperatures (Fig.…”
Section: No-choice Experimentscontrasting
confidence: 90%
See 1 more Smart Citation
“…Our results also contrasted with another report that indicated resistance in LD05-16611 (Rag1) to aphid biotypes 1 and 3 was ineffective at 14°C (Richardson, 2012). Results in this study indicated that resistance expression in LD05-16611 kept aphid populations at similar levels in all three temperatures (Fig.…”
Section: No-choice Experimentscontrasting
confidence: 90%
“…2). Furthermore, it was reported that PI 200538 (Rag2) expressed resistance to aphid biotype 3 at 21 and 28°C (Richardson, 2012), which directly contradicts the fact that the aphid biotype 3 was virulent on PI 200538 and has been maintained on other soybean genotypes with Rag2 as susceptible checks at temperatures within 21 to 28°C in several studies (Alt and Ryan-Mahmutagic, 2013;Bansal et al, 2013;Fox et al, 2014;Hill et al, 2010;Kim et al, 2014). Richardson also reported that the antixenosis-type resistance against aphid biotypes 1 and 3 in PI 567597C was reduced at 28°C, which was not found in this study (Fig.…”
Section: No-choice Experimentsmentioning
confidence: 99%
“…The variation among temperatures used for these experiments could be a possible explanation for the differences in results. Furthermore, there may be interactions between abiotic factors, like temperature, on the impact of Rag genes [ 37 , 38 ]. However, the extent that the protection from all Rag genes is influenced by temperature is unknown [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its economic importance and recent introduction to North America, most studies on A. glycines have focused on documenting the biology and genetics of this species in the USA (Kim et al 2008;Michel et al 2009;Richardson 2012;Jun et al 2013;Swenson et al 2014). Recently, much effort has been made to identify the origin of invasive populations in North America, but these have been largely based on limited samples.…”
Section: Introductionmentioning
confidence: 99%